First results on an elite-level transtibial amputee athlete from a sport-focused motion analysis protocol - Raggi, M.; Cutti, A.G.; Boccafogli, E.; Verni, F. (Gait and Posture, 2011)
The INAIL Prostheses Centre has recently initiated a collaboration with the Italian Paralympic Committee to support elite-level athletes with biomechanical evaluations. A protocol to assess running performance was developed and is presented here considering an elite-level athlete. The aim of the protocol is to provide significant performance outcomes without encumbering the athlete, thus using only "non-contact" instrumentations, i.e. a high speed camera and the Optojump system (Microgate, I).